Mengkaji Metode Tafsir oleh Abdullah Saeed - Rafikah Marhani Hsb; M. Riswandi; Unaisyah Syalsyaqila (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study examines the contextual interpretation method developed by Abdullah Saeed, a progressive Muslim scholar who embraces a modern approach to understanding the Qur'an. This approach was created in response to textual interpretation methods in understanding the meaning of Qur'anic verses. Saeed emphasizes the importance of understanding revelation in its social and historical context so that Islamic teachings remain relevant to the times. One of the main concepts in this interpretation method is the hierarchy of values, which distinguishes between immutable and mutable teachings. This research uses a qualitative approach with a focus on literature, analyzing the works of Abdullah Saeed and previous research. The results of the research show that Saeed's Contextual Exegesis method is able to provide a more flexible understanding of the Qur'anic text, especially in verses related to law and ethics. One example of its application is the interpretation of the verse on the hijab in QS. Al-Ahzab: 59, where Saeed emphasizes that the command to wear the hijab has a specific social context that must be understood before being applied in modern life. This approach has broad implications for contemporary Islamic studies, particularly in addressing various social and legal challenges. However, this method has also faced criticism from conservative circles who argue that contextualization may obscure the original meaning of the Qur'an. Therefore, further research is still needed to explore its application in various aspects of Islamic life.